PERENCANAAN STRATEGI PENDIDIKAN ANAK USIA DINI HOLISTIK INTEGRATIF UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN ANAK USIA DINI DI PG ANAK CERIA KOTA BANDUNG - Deni Tirta Pawana Putra; Elistiana Wulan Sari; Eneng Robi’ah; Sri Handajani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the strategic planning of Holistic IntegrativeEarly Childhood Education (PAUD-HI) to improve the quality of studentlearning. The background of this research is based on the importance ofa comprehensive and integrated service approach for early childhood, asmandated by Presidential Regulation No. 60 of 2013. This researchemploys a descriptive qualitative method with data collection techniquesincluding observation and document analysis at early childhoodeducation institutions. The findings reveal that the implementation ofPAUD-HI is not yet optimal due to limited resources, inadequateinfrastructure, and lack of cross-sector coordination. Strategic planningin PAUD-HI includes education, health, nutrition, protection, and child welfare in an integrated manner. In practice, learning should be child-centered, using play-based and meaningful activities, with active involvement of teachers and support from families and partnerinstitutions. This study recommends strengthening managerial functions,enhancing teacher training, and improving cross-sector collaboration toachieve quality PAUD-HI services.